Desempenho dinâmico de sistemas elétricos industriais com grandes cargas motóricas e geração síncrona - Valle, Rodrigo Luiz de Souza (2018)
Industrial electrical systems that are disconnected from the national electrical system are systems more vulnerable to the more common transient events, so that the evaluation of their performance is even more critical. As an example of this type of system, one can cite the oil production platforms. These platforms have experienced a significant increase in processing capacity, which, in turn, implies an increase in the size of their electrical systems. The electrical system not only started to have more loads, but also bigger loads. In addition, other large loads have changed their form of operation, for example, produced gas compressors that are no longer driven by turbines and are now driven by electric motors, even under direct starting conditions. In this context, this dissertation focused on the study and comparison of the dynamic behavior of the electrical system under certain contingencies when using generators with rotating brushless exciter and when using generators with static exciters and brushes.